'Smart city' system as an asset of cultural landscapes development. Issue 1 (March 2020) - Blagovidova, N G; Iudina, N V
Abstract: The article touches upon the idea of 'smart city' and ways of how it could be applied to advancing contemporary urban environment. Highlighting variety of definitions this popular term demonstrates there is posed a problem of apprehension both in theory and architectural practice. Authors place particular importance on social aspects of the method to be improved to make it adaptable to integrate with cultural heritage. Having referred to successful examples of heritage technological improvement authors claim 'smart city' to possess a level of 'transparency' high enough to create the superstructure of urban history basis, which is particularly significant for small towns and settlements of Russia. Finally ' smart technologies' pretend to be an efficient strategy in Russian dispersal system for consistency enhancement.